The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/cssc.201600063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ligands on the Formation of Kesterite Thin Films for Solar Cells: A Comparative Study

Abstract: The preparation of solar-cell-grade Cu2 ZnSnS4 (CZTS) thin films from ligand-capped small-grained CZTS particles remains hindered by problems of phase segregation, composition non-uniformity, and in particular carbon-layer formation. Herein, through a systematic comparative study of annealed films of CZTS nanocrystals prepared using conventional oleylamine and those prepared using formamide, these problems are found to be mainly attributable to the influence of the ligands, and mechanisms are proposed. Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…2(c) as no such bottom FG layers are obtained in carbon free techniques. [20][21][22] The small network of grain boundaries in the FG layer may contribute high series resistance and reduce the fill factor of solar cells. 11,23,24) It is difficult to draw conclusions about the total thickness of the entire film due to the combination of uncertainty in the precursor thickness (nominally 1.0 ± 0.1 µm) and surface roughness however, it can be clearly seen that as the thickness of the FG layer increases, the MoSe 2 layer becomes thinner.…”
Section: Resultsmentioning
confidence: 99%
“…2(c) as no such bottom FG layers are obtained in carbon free techniques. [20][21][22] The small network of grain boundaries in the FG layer may contribute high series resistance and reduce the fill factor of solar cells. 11,23,24) It is difficult to draw conclusions about the total thickness of the entire film due to the combination of uncertainty in the precursor thickness (nominally 1.0 ± 0.1 µm) and surface roughness however, it can be clearly seen that as the thickness of the FG layer increases, the MoSe 2 layer becomes thinner.…”
Section: Resultsmentioning
confidence: 99%
“…Table S1. CZTS nanoparticles were fabricated using a hot-injection method where a sulphur-OLA solution was injected into a hot metallic precursors-OLA solution (Qu et al, 2014). The resulting nanoparticle inks were deposited on molybdenum substrates via spin coating to form the CZTS precursor thin lm with a thickness around 1 µm (Qu et al, 2016a).…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al recently suggested the use of formamide (FA) instead of OLA to produce single CZTS absorber layer without the FG layer (Huang et al, 2015). Surprisingly, despite a complete comparison of the microstructure properties of the absorber layer (Huang et al, 2016), there is no functional device reported from nanoparticle synthesized with FA. In this paper, we demonstrate working solar cells using a dual ligands approach via a stack of FA and OLA based absorbers: the FA absorber is used to provide a reduced back contact barrier height while the OLA absorber ensures a functioning pn-junction.…”
Section: Introductionmentioning
confidence: 99%